The Issue of Enacting the Omnibus Law on Job Creation from the Perspective of Indonesian Constitutional Law - Aryuni Fitri Djaafara (Asian Journal of Social and Humanities, 2023)
The formation of the Job create law is one of breakthroughs that government has in the field of law to improve overlapping regulations, in particular conflicting or similar laws and regulations and then changes to regulations will be made. The purpose of this writing is to figuring the problem to makes occurs in formation of the law labor through Law Number eleven 2020 years concerning work creation. The formulation of the Job Creation Law uses the Omnibus Law approach by drafting laws that have different principles from one another. This approach was chosen with the hope of making licensing simpler and more accessible to investors and could have a positive impact on economic growth and employment. At the time of writing, the author using normative legal methods like collecting data from products in the area of law. With the birth of the law creating jobs should be hoped that it can increase investment so that it can create as many jobs as possible to reduce unemployment. And the government can issue regulations that benefit employers and workers so that they can comply with regulations that protect workers' rights. Because labor is a major part of the running process of a company.